Encounters Old and New in World History : Essays Inspired by Jerry H. Bentley - Bentley, Jerry H., 1949-2012; Mitchell, Laura Jane, 1963-; Karras, Alan L. (Book collections on Project MUSE., 2017)
This volume asserts the specific value of world history research and teaching, showing how the field contributes to the larger historical profession and offering concrete suggestions to develop more interaction between the academy and the public. The twelve contributors, each with their own academic areas of interest, are experienced scholars and classroom teachers.